2023
DOI: 10.3390/pharmaceutics15041252
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Targeted Therapy and Immune-Checkpoint Inhibition in Lung Cancer

Abstract: Lung cancer (LC) represents the second most diagnosed tumor and the malignancy with the highest mortality rate. In recent years, tremendous progress has been made in the treatment of this tumor thanks to the discovery, testing, and clinical approval of novel therapeutic approaches. Firstly, targeted therapies aimed at inhibiting specific mutated tyrosine kinases or downstream factors were approved in clinical practice. Secondly, immunotherapy inducing the reactivation of the immune system to efficiently elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 283 publications
0
10
0
Order By: Relevance
“…It has been suggested that, in the case of cardiomyocytes, stimulation of the TRPM2 channel, as well as poly(ADP-ribose) polymerase, is expected to be engaged in oxidative stress-prompted cell death [ 54 ]. In cancer, the production of ROS by mitochondria promotes cellular oncogenesis by shaping signaling pathways and specific transcription factors [ 55 ]. TRPM2 maintains the bioenergy of cancer cells by maintaining mitochondrial activity and increased ROS production [ 38 , 56 ].…”
Section: Rpm2 Channel: a Brief Overviewmentioning
confidence: 99%
“…It has been suggested that, in the case of cardiomyocytes, stimulation of the TRPM2 channel, as well as poly(ADP-ribose) polymerase, is expected to be engaged in oxidative stress-prompted cell death [ 54 ]. In cancer, the production of ROS by mitochondria promotes cellular oncogenesis by shaping signaling pathways and specific transcription factors [ 55 ]. TRPM2 maintains the bioenergy of cancer cells by maintaining mitochondrial activity and increased ROS production [ 38 , 56 ].…”
Section: Rpm2 Channel: a Brief Overviewmentioning
confidence: 99%
“…The most important anticancer mechanisms are summarized in Lung cancer, predominantly caused by prolonged tobacco smoking, remains the leading cause of cancer-related mortality worldwide. Its complex heterogeneity, with non-small-cell lung cancer being the most common subtype, underscores the imperative need for early detection and individualized therapeutic strategies (Leone et al, 2023). EMT is linked with metastasis, invasiveness, tumorigenesis, and therapeutic resistance (Pastushenko & Blanpain, 2019).…”
Section: Anticancer Effects and Mechanisms Of β-Sitosterolmentioning
confidence: 99%
“…During metastasis, EMT conferred migratory as well as invasive capacity to cancerous cells. Following the induction of EMT, cancer cells depicted bolstered aggressive stem-like features and become rebellious to apoptosis (Leone et al, 2023;Suarez-Carmona et al, 2017). β-sitosterol has inhibited transforming growth factor-β1 (TGF-β1)-induced EMT in human alveolar epithelial cells and consequently attenuated the pulmonary fibrosis.…”
Section: Anticancer Effects and Mechanisms Of β-Sitosterolmentioning
confidence: 99%
“…However, it demonstrated an increase trend in incidence in female in China ( 8 ). Although new treatment strategies, such as targeted therapies that inhibit specific mutated tyrosine kinases or downstream factors ( 9 ), immunotherapy that reactivates the immune system to eliminate LC cells ( 10 ), novel multi-tier biotechnology treatments ( 1 , 11 ), and etc ( 12 , 13 ), have emerged, the success rate of therapy remains relatively low. Moreover, the prognosis for late-stage lung cancer patients is worse than for other types of cancer.…”
Section: Introductionmentioning
confidence: 99%